Fertility preferences and subsequent childbearing in Africa and Asia: A synthesis of evidence from longitudinal studies in 28 populations. (2nd January 2020) - Cleland, John; Machiyama, Kazuyo; Casterline, John B.
Abstract : Survey data on fertility preferences have played a central but controversial role in fertility research and advocacy for family planning. We summarize evidence from longitudinal studies in 28 Asian and African populations on the relationship between preferences and subsequent childbearing. While we found no consistent association between women's desire to delay childbearing and subsequent fertility, the baseline desire of women to stop childbearing was a powerful predictor of subsequent fertility in all populations and increased in strength as overall contraceptive use in the study populations rose. Partners' desire also exercised some influence but was of modest importance in most populations. However, the correspondence between desire to stop and behaviour was found to be far from perfect. Weak implementation of preferences by contraception is likely to be the major cause of this preference–behaviour discrepancy. Uncertainty and instability in preferences may also contribute to the discrepancy, particularly in sub-Saharan Africa .